Algorithm for teaching students of the special educational department of physical education - Egorychev, Aleksey O.; Egorycheva, Elina V. (Физическое воспитание и студенческий спорт)
Among students with health restrictions, a high proportion has a passive level of needs for physical education and sports activities. It is topical to create pedagogical conditions for a gradual transition from a passive state to a situational or active-activity state in relation to physical education and sports activities. The algorithm for teaching such students is shown, which includes teaching the skills to correctly select aerobic load, to perform available sets of exercises for flexibility and strength, taking into account the functional level and nosological form.